Patterns of fluoride intake from 6 to 17 years of age: The Iowa Fluoride Study. (17th October 2022) - Bhagavatula, Pradeep; Comnick, Carissa L.; Warren, John J.; Levy, Steven M.
Abstract: Objectives: This article reports on estimated daily fluoride intake from water, other beverages and selected foods, dentifrice, and dietary fluoride supplements by both individual sources, and all sources combined, among 787 children participating in the Iowa Fluoride Study (IFS) from 6 to 17 years of age. Methods: Total daily fluoride intake (mg F) and fluoride intake per kilogram bodyweight (mg F/kg bw) were estimated using responses to questionnaires sent every 3–6 months. Dietary assessments included frequencies and amounts of beverage intake for the previous week from water, milk, ready‐to‐drink beverages, beverages made by adding water to concentrate or powder, and selected foods with substantial water content. Descriptive statistics and bivariate and multivariable analyses with linear mixed models were used to assess associations with each of mg F and mg F/kg bw. Results: Mean combined dietary fluoride (mg F) from all sources examined in the study increased slightly with age, whereas the fluoride intake per kg bw decreased with age. Age, sex, and socioeconomic status were significantly associated with fluoride intake (mg F and mg F/kg bw). Each year increase in age was associated with a 0.02‐mg increase in fluoride consumption, on average, after adjusting for the effects of covariates. Conclusions: Daily mean fluoride intakes from single and combined sources were relatively stable, while the intake of fluoride per kg bw decreased from 6 to 17 years of age. Fluoridated water was the major source of ingested fluoride, contributing over 50% of total daily intake at all ages.